Data on the concentrations of etoposide, PSC833, BAPTA-AM, and cycloheximide that do not compromise the vitality of mature mouse oocytes, parthenogenetically activated and fertilized embryos - Jacinta H. Martin; Elizabeth G. Bromfield; R. John Aitken; Tessa Lord; Brett Nixon (Data in Brief, 2016)
These data document the vitality of mature mouse oocytes (Metaphase II (MII)) and early stage embryos (zygotes) following exposure to the genotoxic chemotherapeutic agent, etoposide, in combination with PSC833, a selective inhibitor of permeability glycoprotein. They also illustrate the vitality of parthenogenetically activated and fertilized embryos following incubation with the calcium chelator BAPTA-AM (1,2-Bis(2-aminophenoxy)ethane- N,N,N′,N′-tetraacetic acid tetrakis (acetoxymethyl ester)), cycloheximide (an antibiotic that is capable of inhibiting protein synthesis), and hydrogen peroxide (a potent reactive oxygen species). Finally, they present evidence that permeability glycoprotein is not represented in the proteome of mouse spermatozoa. Our interpretation and discussion of these data feature in the article “Identification of a key role for permeability glycoprotein in enhancing the cellular defense mechanisms of fertilized oocytes” (Martin et al., in press) [1]. Keywords: Oocytes, Parthenote, Embryo, Vitality, Etoposide, PSC833, BAPTA-AM, Cyloheximide